2023
DOI: 10.3390/su15020947
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of China’s Pilot Free Trade Zones on Green and High-Quality Development from the Dual-Circulation Perspective

Abstract: Under the dual pressure of economic growth and environmental pressure, green and high-quality development become a critical strategy for China to achieve win-win development for both the economy and the environment. In the dual-circulation pattern, a deep and high level of openness is the primary prerequisite for encouraging green and high-quality development. Previous studies have overlooked the crucial pivotal role of pilot free trade zones (PFTZs) in domestic and international circulation. The PFTZ is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Empirical studies by Jiang et al [37] and Ma et al [38] on the Shanghai PFTZ revealed significant institutional dividends and a positive correlation between PFTZs and GTFP, albeit with diminishing effects over time. Furthermore, Chang et al [2] found that the establishment of PFTZs significantly fosters regional green and high-quality development, while Zhang and Zhou [8] identified that PFTZs enhance regional green total factor energy efficiency through industrial structure upgrades and promotion of green technological innovation.…”
Section: Pftz Policy Impact On Urban Green Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies by Jiang et al [37] and Ma et al [38] on the Shanghai PFTZ revealed significant institutional dividends and a positive correlation between PFTZs and GTFP, albeit with diminishing effects over time. Furthermore, Chang et al [2] found that the establishment of PFTZs significantly fosters regional green and high-quality development, while Zhang and Zhou [8] identified that PFTZs enhance regional green total factor energy efficiency through industrial structure upgrades and promotion of green technological innovation.…”
Section: Pftz Policy Impact On Urban Green Developmentmentioning
confidence: 99%
“…Columns (2) and (3) display the regression results related to the mechanism of technological progress. Column (2) indicates that PFTZ has a significant positive effect on the mediator variable TECH, suggesting that the establishment of PFTZ can notably enhance technological progress. From column (3), it can be observed that technological progress significantly promotes GTFP.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation